EVALUASI ESTETIKA LASKAP PESISIR KAWASAN WISATA PANTAI KOKA MAUMERE FLORES NTT - Putra, Alendro N. Djea M. L.; Alfian, Rizki; Nailufar, Balqis (Fakultas Pertanian, 2019)
Koka Maumere Beach Coastal Area is an area that has a variety of natural resources that can be developed into tourist objects and attractions. Koka Maumere Beach has the potential of natural resources, a distinctive and beautiful visual landscape with friendly locals, as well as the availability of natural objects and interesting cultural activities of local people in the coastal area of Koka Beach. With the tourism landscape planning, Koka Beach is expected to improve environmental quality, preserve natural resources, and preserve local culture, and increase the income of local communities. The purpose to be achieved through the research in question is to determine and assess the visual quality of the tourist area of Koka Beach based on the estimation of beauty. Based on the SBE value, Koka Beach in landscape 28 has the highest visual value of 71.786-171.164, medium, which is 40.624-67.855, and the lowest is 00.00-37,428. High beauty classification (T) has a blend of built and natural landscapes that create a landscape with cultural characteristics, moderate (S) beauty classification because sand and green vegetation give a shady and natural beach impression, and a low (R) beauty classification due to the coastal landscape less beautiful, thus reducing aesthetics. Kawasan Pesisir Pantai Koka Maumere merupakan kawasan yang memiliki beragam sumber daya alami yang dapat dikembangkan menjadi objek dan atraksi wisata. Pantai Koka Maumere memiliki potensi sumberdaya alam, visual lanskap yang khas dan indah dengan penduduk setempat yang ramah, serta tersedianya objek alam dan aktivitas budaya masyarakat lokal yang menarik di kawasan pesisir Pantai Koka. Dengan adanya perencanaan lanskap wisata diharapkan dapat meningkatkan kualitas lingkungan, melestarikan sumberdaya alam, dan melestariakan budaya lokal, serta meningkatkan pendapatan masyarakat lokal. Tujuan yang akan dicapai melalui penelitian yang dimaksud adalah menentukan dan menilai kualitas visual kawasan wisata Pantai Koka berdasarkan pendugaan keindahan. Berdasarkan nilai SBE Pantai Koka pada lanskap 28 memiliki nilai visual tertinggi yaitu 71,786-171,164, sedang yaitu 40,624-67,855, dan terendah yaitu 00,00-37,428. Klasifikasi keindahan tinggi (T) terdapat perpaduan lanskap binaan dan alami yang menciptakan lanskap yang berkarakter budaya, klasifikasi keindahan sedang (S) dikarenakan hamparan pasir dan hijaunya vegetasi memberikan kesan pantai yang teduh dan alami, dan klasifikasi keindahan rendah (R) dikarenakan lanskap pantai yang kurang indah, sehingga mengurangi estetika.